Confirmation, Meaning and Self-Awareness as Core Concepts of the Nursing Supervision Model - Severinsson, Elisabeth I (Nursing ethics, 2001)
The general objective of nursing supervision is to support the development of the super-visee’s job identity, competence, skills and ethics. This can be achieved through the stages of the supervision process. The aim of this article is to describe and discuss such a nursing supervision model, as well as the supervisor’s competence and moral responsibility, by analysing the interpretation of nursing supervision. Three main concepts are described: confirmation, meaning and self-awareness. The findings suggest that these concepts need to be established in the nursing supervision process by the supervisor, who is morally responsible for applying the process and for establishing a relationship with the supervisees.